2023
DOI: 10.3390/foods12091789
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Rheological Characteristics of Commercial and Monovarietal Wheat Flours from Peru

Abstract: In Peru, wheat (Triticum aestivum L.) is one of the main resources in the food industry; however, due to its low harvested area, it is the second most imported cereal. The quality of wheat flour was studied to verify that it has desirable characteristics for the preparation of bakery products. The quality of commercial and monovarietal wheat flours was assessed by measuring their physicochemical and rheological parameters, as well as the gluten content and wheat protein fractions. Eight commercial wheat flours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…12.02% and from 8.26% to 12.85% [42,43]. Moreover, in a comparison of commercial and monovarietal wheat flour from Peru, it was found that the average protein level was 9.64% and 8.02%, respectively [40]. Lipids are found throughout the wheat grain and mainly in the germ and aleurone, with a relatively smaller amount in the endosperm [44,45].…”
Section: Proximate Compositionmentioning
confidence: 98%
See 1 more Smart Citation
“…12.02% and from 8.26% to 12.85% [42,43]. Moreover, in a comparison of commercial and monovarietal wheat flour from Peru, it was found that the average protein level was 9.64% and 8.02%, respectively [40]. Lipids are found throughout the wheat grain and mainly in the germ and aleurone, with a relatively smaller amount in the endosperm [44,45].…”
Section: Proximate Compositionmentioning
confidence: 98%
“…The protein content is related to both genetic and non-genetic variables because nitrogen-rich soils may modify protein levels [40,41]. In Table 3, it is also visible that the percentage of proteins varied from 8.06 ± 0.01 (C0) to 10.54 ± 0.03 (R1) with 9.47 as the average.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Even though there was a considerable difference in the crude fat and ash contents, the differences observed are almost similar in industrial settings. Ash is an important attribute of flour as it denotes the extent of bran contamination in the flour, which can lead to negative effects to its functionality (e.g., inhibit gluten formation) (Best et al, 2023). Changes in the flour milling yields could be attributed to bran contamination as there is a limit on how much endosperm can be extracted from the grains.…”
Section: Flour Quality Evaluationmentioning
confidence: 99%
“…Protein content of wheat varies between 7% and 18% and the proteins that form gluten constitute a large part (around 80%) of the total proteins (Shewry et al, 1997;Peña et al, 2002;Uthayakumaran and Wrigley, 2017;Guzmán et al, 2022). In general, the quality of wheat flour for bread making is evaluated by the amount of protein and the quality of gluten (Best et al, 2023), as gluten is the main network-forming protein in wheat flour with its ability to impart the desired viscoelasticity to dough (Yazar et al, 2017a). The viscoelastic properties of the gluten network formed upon hydration of flour particles during mixing help dough retain gas to obtain the desired loaf volume and crumb texture in bread (Shewry et al, 1997;Uthayakumaran and Wrigley, 2017;Yazar et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Gluten properties and functionality can be determined either using the physicochemical tests such as Gluten wash, Zeleny sedimentation; or it can be measured by testing the rheological properties of the whole wheat flour dough through the empirical methods including Farinograph, Extensograph, Mixograph, and Alveograph tests (Uthayakumaran and Wrigley, 2017;Best et al, 2023). Empirical methods have demonstrated their usefulness in industry and research to relate the rheological behavior of dough to baking performance, they have the disadvantage of providing data in arbitrary units, which makes the fundamental interpretation of results difficult (Campanella and Peleg, 2002;Dobraszczyk and Morgenstern, 2003).…”
Section: Introductionmentioning
confidence: 99%